(untitled) (Sciences & Technology. A, exactes sciences, 1999)
Aluminium alloys can be thermomechanically processed to develop the grain fine microstructures required for superplasticity by either static recrystallisation prior to superplastic forming (SPF) or by dynamic recrystallisation during the early stages of deformation. The present work has examined and compared the superplastic behaviour and the microstructural evolution in Al-Li alloys (8090) sheet material processed by the second route for a wide range of temperatures and strain-rates. It was observed that the material showed a high potential for superplastic flow. Although significant superplasticity was observed at temperature of 400°C and below. The reasons for the high resistance of the material to strain localisation are discussed. It was noted that ductility enhancement could also be achieved by the control of the strain-rate path. A rapid pre-strain improved significantly the subsequent superplastic elongation to failure at optimum strain rate. Further enhancement has been obtained by pre-straining at constant velocity following by deformation to failure at lower constant velocity. The microstructure changes prior or during deformation were also examined.